Characterization of Some Commercially Important Octopus (Mollusca: Cephalopoda) from Indonesian Waters using Mitochondrial DNA Cytochrome Oxidase Sub-Unit I (Mt-DNA COI) - Nenik Kholilah; Norma Afiati; Subagiyo Subagiyo (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
As per the FAO data, octopus identification is very limited in the species level at world fishery and also they are cryptic nature. On the other hand, Indonesia is one of the top ten highest octopus exporters. This study therefore aimed to determine the species of octopus based on phylogenetic analysis of mt-DNA COI. Octopuses were collected from nine different locations throughout Indonesia, i.e., Anambas, Bangka-Belitung, Cirebon, Karimunjawa, Tuban, Lombok, Buton, Wakatobi and Jayapura. Samples were mostly in the form of tentacles that were directly collected from fishermen. After being preserved in 96% ethanol, the sample was extracted in 10% chelexÒ, PCR amplification using Folmer’s primer then was further analysed by sequencing in Sanger methods. Of the 24 samples sequenced, the results recognized four species Octopodidae belongs to the three genera, named Amphioctopus aegina, Hapalochlaena fasciata, Octopus laqueus and Octopus cyanea. Mean pair-wise distances of within-species were ranged from 0 to 5.5 % and between-species was ranged from 12.9 to 15.8 %. This study distinctly confirmed the difference between genus Amphioctopus and Hapalochlaena (15.5 %), as also between O. laqueus and O. cyanea (12.9%) which was previously not completely distinguished. Although performing species identification using DNA sequences for shallow-water benthic octopus species is perhaps considered premature, this study indicated the possible application of COI sequences for species identification, thereby providing a preliminary dataset for future DNA barcoding of octopus, in particular for Indonesia waters.